Criminal Liability of Parents Who Abandon Children With Disabilities - Ni Nyoman Muryatini (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2019)
Not all parents sincerely accept and give affection to children with disabilities. Disabled children are still considered a disgrace from the family therefore so many cases of children to abandon with disabilities carried out by their own parents. Humans are creatures created by the Almighty God who has the same position. Every human being has the dignity and inherent of humanity. This condition should not be the cause of the dignity lose of children with disabilities or an excuse for not aligning them with other children. Indonesia guarantees the survival of every citizen, including persons with disabilities who have the same legal and human rights position as Indonesian citizens. The act of abandoning children with a disability is a crime that must be held a liability to each of the perpetrators including both the children’s parents and children who are victims of abandoning from their parents must obtain legal protection from the government. This research is analyze the criminal liability of parents who abandon children with disabilities. The method used was normative law which aimed at finding and formulating legal arguments, through analysis of the subject, the approach used in this study was legislation approach by examining the applicable legal rules related to criminal liability of parents who abandon children with disabilities.